Comparison of intraspinal and intrathecal implantation of induced pluripotent stem cell-derived neural precursors for the treatment of spinal cord injury in rats. Issue 1 (December 2015) - Amemori, Takashi; Ruzicka, Jiri; Romanyuk, Nataliya; Jhanwar-Uniyal, Meena; Sykova, Eva; Jendelova, Pavla
Abstract Background Stem cell treatment provides a promising therapy for patients with spinal cord injury (SCI). However, the applied stem cells exert their effects in different manners that are dependent on the route used for administration. Methods In the present study, we administered neural precursors derived from induced pluripotent stem cells (iPS-NPs) either intraspinally into the lesion center or intrathecally into the subarachnoid space of rats with a balloon-induced spinal cord compression lesion. Functional locomotor performance, cell survival, astrogliosis, axonal sprouting and the expression of endogenous neurotrophic growth factors were evaluated using behavioral tests (BBB, flat beam test, rotarod, plantar test), morphometric analysis, immunohistochemistry and qPCR. Results Both treatments facilitated the functional locomotor recovery of rats with SCI. iPS-NPs injected intraspinally survived well for 2 months and were positive for MAP2, while cells grafted intrathecally were undetectable at the site of administration or in the spinal cord tissue. Intraspinal implantation increased gray and white matter sparing and axonal sprouting and reduced astrogliosis, while intrathecal application resulted only in an improvement of white matter sparing and an increase in axonal sprouting, in parallel with no positive effect on the expression of endogenous neurotrophic growth factor genes or glial scar reduction. Conclusions Intrathecally grafted iPS-NPs had a moderate therapeutic benefit on SCI through a paracrine mechanism that does not require the cells to be present in the tissue; however, the extended survival of i.s. grafted cells in the spinal cord may promote long-term spinal cord tissue regeneration.